PENGARUH TERPAAN BERITA HOAX "PENGANIAYAAN RATNA SARUMPAET" DI MEDIA ONLINE KOMPAS.COM TERHADAP SIKAP PEMILIH PELAJAR KEPADA CALON PRESIDEN PRABOWO SUBIANTO : Survei pada siswa SMAIT Pesantren Nururrahman kelas 12 - Muhammad Ramadhitya Hasabi, - (2019)
The background of this study discusses how much the effect of the hoax news exposure is "the persecution of Ratna Sarumpaet" on the attitude of student voters to candidate President Prabowo Subianto. This research was conducted using a quantitative approach. The research method used is a survey. The theory used in this study is the theory of S - O - R. This type of research is explanatory. The sampling technique uses a saturated sample technique where the researcher takes the total population. Data analysis techniques Variables X and Y Variables using the coefficient of determination test. The data collection technique is processed using SPSS version 25 and 16. The results of this study indicate that the correlation of X and Y Variables is 0.262. Based on the results of the calculation of the coefficient of determination obtained results of 6.8% with the calculation of t count <t table is 3.39 <1.66365, it can be concluded that there is no influence between news hoax exposure "persecution of Ratna Sarumpaet" on kompas.com online media towards voter attitudes student to candidate President Prabowo Subianto.